Les tactiques de l'interprète en langue des signes face au vide lexical : une étude de cas - Pointurier Pournin, Sophie; Gile, Daniel (The Journal of Specialised Translation, 2012)
French Sign Language has a far smaller specialised lexicon than French, which poses regular problems to interpreters working between the two. Four management control sessions attended by a deaf student and interpreted for him by four professional interpreters were recorded, and the interpreters' tactics when encountering the problems of missing signs in French Sign Language ('lexical gaps') were identified, counted and analyzed. Lexical gaps were found to be numerous in the corpus. The tactics often used elements of French spoken language, in contradiction with a strong sociolinguistic norm in the French deaf community. This can be explained by the interpreters' wish to cater to the needs of the deaf student, who needed to know the French terms when taking exams, and is in line with skopos theory.